Taxonomic study of Chinese species of the genus Macropsis Lewis, 1836 (Hemiptera: Cicadellidae: Macropsinae) II: a new subgenus for Macropsis flavovirens Kuoh - Li, Hu; Dai, Ren-Huai; Li, Zi-Zhong; Tishechkin, Dmitri Yu. (Zootaxa, 2013)
A new monobasic subgenus, Macropsis (Spinomacropsis) subgen. nov., of the subfamily Macropsinae (Hemiptera: Auchenorrhyncha: Cicadellidae) based on type species Macropsis flavovirens Kuoh, 1992 from Yunnan Province of China is proposed. The new subgenus can be distinguished by the unique character of the male pygofer with two spinelike pro-cesses on the caudal margin. Macropsis (S.) flavovirens is redescribed and illustrated, and data on its geographical distri-bution are given.